Aceh Rencong Making in Baet Village, Aceh Besar District as A Preserved Cultural Heritage - Nana Novita; Irwan Irwan; Ida Hasanah (International Conference on Multidisciplinary Research, 2022)
This journal is entitled "The Development of Aceh Rencong Making in Baet Village, Aceh Besar Regency as a Cultural Heritage that is Still Preserved". The purpose of this study is to describe how the development process of Rencong Aceh in the Aceh Besar area, namely in the villages of Baet Meusago and Baet Lampuot, to describe what efforts were made by the makers and stakeholders so that Rencong Aceh remains a tangible cultural heritage in this era. globalization now. This study uses a descriptive research method with a qualitative approach because the problems to be studied are dynamic and complex. The data collection techniques are observation, structured interviews, documentation and other supporting books from the library that are related and lead to the research title. The results showed that the development of the Aceh Rencong making in the two villages underwent changes starting from the materials used, manufacturing procedures and the most prominent was experiencing changes in function according to the times and field conditions in the two villages where Rencong research was carried out as sharp objects and tools. stab is no longer produced. television, there are orders from the public. This is caused by several problems that exist in the field, namely the lack of attention from local communities and outsiders, and the required capital is greater. So that the craftsmen of Rencong as a stabbing tool switch to other innovations such as in Baet Meusago village making Rencong key chains and Baet Lampout village making Rencong souvenirs. Despite the changes, Rencong remains the main theme of the village. Although the resulting product has undergone changes, Rencong is still its main identity that continues to be preserved and maintained. Keywords: History, Rencong Aceh, Baet Village, Aceh Besar, Cultural Heritage.